Long-term outcome on renal replacement therapy in patients who previously received a keto acid-supplemented very-low-protein diet - Chauveau, Philippe; Couzi, Lionel; Vendrely, Benoit; de Précigout, Valérie; Combe, Christian; Fouque, Denis; Aparicio, Michel (The American journal of clinical nutrition, 2009)
The consequences of a supplemented very-low-protein diet remain a matter of debate with regard to patient outcome before or after the onset of renal replacement therapy. We evaluated the long-term clinical outcome during maintenance dialysis and/or transplantation in patients who previously received a supplemented very-low-protein diet. We assessed the outcome of 203 patients who received a supplemented very-low-protein diet for >3 mo (inclusion period: 1985-2000) and started dialysis after a mean diet duration of 33.1 mo (4-230 mo). The survival rate in the whole cohort was 79% and 63% at 5 and 10 y, respectively. One hundred two patients continued with chronic dialysis during the entire follow-up, and 101 patients were grafted at least once. Patient outcomes were similar to those of the French Dialysis Registry patients for the dialysis group and similar to the 865 patients who were transplanted in Bordeaux during the same period for the transplant group. There was no correlation between death rate and duration of diet. The lack of correlation between death rate and duration of diet and the moderate mortality rate observed during the first 10 y of renal replacement therapy confirm that a supplemented very-low-protein diet has no detrimental effect on the outcome of patients with chronic kidney disease who receive renal replacement therapy.